Health effects of exposure to sulfur dioxide, nitrogen dioxide, ozone, and carbon monoxide between 1980 and 2019: A systematic review and meta‐analysis. (18th November 2022) - Chen, Zhuoru; Liu, Ningrui; Tang, Hao; Gao, Xuehuan; Zhang, Yinping; Kan, Haidong; Deng, Furong; Zhao, Bin; Zeng, Xiangang; Sun, Yuexia; Qian, Hua; Liu, Wei; et al.
Abstract: The burden of disease attributed to the indoor exposure to sulfur dioxide (SO2 ), nitrogen dioxide (NO2 ), ozone (O3 ), and carbon monoxide (CO) is not clear, and the quantitative concentration–response relationship is a prerequisite. This is a systematic review to summarize the quantitative concentration–response relationships by screening and analyzing the polled effects of population‐based epidemiological studies. After collecting literature published between 1980 and 2019, a total of 19 health outcomes in 101 studies with 182 health risk estimates were recruited. By meta‐analysis, the leave‐one‐out sensitivity analysis and Egger's test for publication bias, the robust and reliable effects were found for SO2 (per 10 μg/m 3 ) with chronic obstructive pulmonary diseases (COPD) (pooled relative risks [RRs] 1.016, 95% CI: 1.012–1.021) and cardiovascular diseases (CVD) (RR 1.012, 95%CI: 007–1.018), respectively. NO2 (per 10 μg/m 3 ) had the pooled RRs for childhood asthma, preterm birth, lung cancer, diabetes, and COPD by 1.134 (1.084–1.186), 1.079 (1.007–1.157), 1.055 (1.010–1.101), 1.019 (1.009–1.029), and 1.016 (1.012–1.120), respectively. CO (per 1 mg/m 3 ) was significantly associated with Parkinson's disease (RR 1.574, 95% CI: 1.069–2.317) and CVD (RR 1.024, 95% CI: 1.011–1.038). No robust effects were observed for O3 . This study provided evidence and basis for further estimation of the health burden attributable to the four gaseous pollutants.